2006
DOI: 10.2353/ajpath.2006.050167
|View full text |Cite
|
Sign up to set email alerts
|

Corticotropin-Releasing Hormone Modulates Human Trophoblast Invasion through Carcinoembryonic Antigen-Related Cell Adhesion Molecule-1 Regulation

Abstract: Abnormalities in the process of trophoblast invasion may result in abnormal placentation. Both the embryonic trophoblast and maternal decidua produce corticotropin-releasing hormone (CRH), which promotes implantation. Carcinoembryonic antigen-related cell adhesion molecule 1 (CEACAM1), which is expressed in extravillous trophoblasts (EVTs) of normal human placenta, may also function in trophoblast/endometrial interactions. We investigated whether locally produced CRH plays a role in trophoblast invasion, prima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(36 citation statements)
references
References 48 publications
3
31
0
2
Order By: Relevance
“…However, instead of promoting growth, we show that CEACAM1 functions to retard several parameters of neoplastic growth and to enhance cell-matrix adhesion. This finding is consistent with the expression of CEACAM1 in extravillous intermediate trophoblast where it has been functionally implicated in mediating trophoblast/endometrial interactions during trophoblastic invasion of the endometrium (Bamberger et al, 2000(Bamberger et al, , 2006, and with its correlation with invasion in cutaneous malignant melanoma (Thies et al, 2002;Ebrahimnejad et al, 2004). These findings can be reconciled by a model in which upregulation of CEACAM1 during cell transformation may reflect a mechanism serving to impede further growth at the expense of promoting metastatic behavior.…”
Section: Ceacam1 In Thyroid Cancer W Liu Et Alsupporting
confidence: 75%
“…However, instead of promoting growth, we show that CEACAM1 functions to retard several parameters of neoplastic growth and to enhance cell-matrix adhesion. This finding is consistent with the expression of CEACAM1 in extravillous intermediate trophoblast where it has been functionally implicated in mediating trophoblast/endometrial interactions during trophoblastic invasion of the endometrium (Bamberger et al, 2000(Bamberger et al, , 2006, and with its correlation with invasion in cutaneous malignant melanoma (Thies et al, 2002;Ebrahimnejad et al, 2004). These findings can be reconciled by a model in which upregulation of CEACAM1 during cell transformation may reflect a mechanism serving to impede further growth at the expense of promoting metastatic behavior.…”
Section: Ceacam1 In Thyroid Cancer W Liu Et Alsupporting
confidence: 75%
“…Corticotropin-releasing hormone, produced both by the trophoblast and the maternal decidua, has been shown to down-regulate expression of the carcinoembryonic antigen-related cell adhesion molecule 1, a cell surface molecule implicated in the invasive potential of EVTs. 41,42 In this study, we investigated for the first time the expression pattern of the metastasis suppressor KAI1 in the utero-placental unit. As shown by immunohistochemistry, strong expression of KAI1 was observed at the maternal-fetal interface, where KAI1 was expressed by the decidual cells and localized to the plasma membrane.…”
Section: Discussionmentioning
confidence: 99%
“…These data further implied that the soluble immune mediators resulting from the direct interaction between trophoblast cells and monocytes may contribute to the increase in the expression of CEACAM1 on the surface of CD4 + CD45RO + T cells, but not on that of CD8 + CD45RO + T cells, in first trimester human decidua. CEACAM1 has been detected on the surface of extravillous trophoblast cells, and is hypothesized to promote the invasion of these cells (33)(34)(35). In addition, numerous studies have demonstrated that CEACAM1 inhibits the cytokine production, proliferation and cytotoxic activity of activated T cells, by homophilic and heterophilic interactions (26)(27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%